(untitled) (Agroindustrial Science, 2020)
The objective of this research study was to develop a traditional and innovative food product such as lyophilized dehydrated inchicapi (peanut soup with cultural and culinary in value the Amazon community of Peru) by lyophilization, which allows the product’s useful life to be extended, maintaining its physicochemical and sensory properties, and make it suitable for human consumption. These products underwent different treatment pressures of 0.05 mbar, 0.1 mbar and 0.16 mbar and thicknesses of 8 mm and 10 mm were used, as appropriate. 30 days after the product was made, the organoleptic analysis determined that the T6 treatment (thickness of 10 mm and pressure 0.16 mbar) is the one with the best attributes with a score of 7.2. Also, the proximal chemical and microbiological analyzes gave as results: humidity: 5.13%; fat: 39.0%; fiber: 7.3%; ash: 2.82%; protein: 21.42%; carbohydrates: 29.46% and energy: 554.5 kcal; evidencing good nutritional quality, a guarantee of product stability; as well as the presence of microorganisms below the standards allowed by Peruvian regulations. Concluding that the freeze-drying of the inchicapi allows us to develop a product that preserves the values of importance for the consumer.